Another piece of the puzzle : firms' investment in training as production of optimal skills inventory - Pfeifer, Harald [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2018)
"By applying the inventory theory to hiring skilled workers under uncertainty, the authors explain how firms decide on their optimum investment in an 'inventory of skills'. This paper investigates the conditions under which firms are willing to make investments in a skilled workforce themselves rather than relying on skills produced within the education system or by other companies. By applying inventory theory to investments into apprenticeship training, the authors explain how firms decide on producing an optimum 'inventory of skills' today to meet future demand. The authors derive hypotheses on how much firms are willing to invest in having a larger inventory of skilled workers depending on different types of inventory costs (overage costs, underage costs, demand structure). The authors use data from the BIBB Cost-Benefit-Survey 2012/2013, which comprises detailed information on different costs and benefits of training investments from the firm's perspective. The study applies a negative binomial estimation model. Results are threefold: firms are willing to invest in a larger inventory of skilled workers, i.e., to train more apprentices, first, if the costs of producing and retaining an excessive number of skilled workers (overage costs) are lower, second, if the costs of being short of skilled workers (underage costs) are higher, and third, given an identical cost structure, if it is more likely that the demand for skilled workers may be high in the future. Even more important is the relationship of the three: the combination of a firm's critical ratio (underage costs in relation to overage costs) with its demand structure (industry volatility) is associated with a higher inventory of skills." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.1 Finanzierungsquellen; G 1.2.3.2 Anforderungen & Bedarfe; Betriebliche Berufsausbildung; Ausbildungsinvestition; Kosten-Nutzen-Analyse; Arbeitsmarktsituation; Fachkräftemangel